2003
DOI: 10.1128/jb.185.12.3654-3660.2003
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Synechococcus sp . Strain PCC 7942: Various Mechanisms for H 2 O 2 Detoxification with Different Physiological Roles

Abstract: This study focuses on the mechanisms for hydrogen peroxide detoxification in Synechococcus sp. strain PCC 7942. To gain better understanding of the role of different routes of hydrogen peroxide detoxification, we inactivated tplA (thioredoxin-peroxidase-like), which we recently identified. In addition, we inactivated the gene encoding catalase-peroxidase and examined the ability to detoxify H 2 O 2 and to survive oxidative stress in both of the single mutants and in the double mutant. Surprisingly, we observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…One of the proteins induced under general stress was identified as a homologue of thioredoxin peroxidase (also designated peroxiredoxin) (Aldehni et al, 2003). This enzyme was shown to be essential for growth under high photon flux (Perelman et al, 2003). Induction of this protein during both sulfur and nitrogen starvation suggests that the trigger for expression may be oxidative stress, which occurs subsequent to nutrient starvation conditions.…”
Section: General Acclimation Responsesmentioning
confidence: 99%
“…One of the proteins induced under general stress was identified as a homologue of thioredoxin peroxidase (also designated peroxiredoxin) (Aldehni et al, 2003). This enzyme was shown to be essential for growth under high photon flux (Perelman et al, 2003). Induction of this protein during both sulfur and nitrogen starvation suggests that the trigger for expression may be oxidative stress, which occurs subsequent to nutrient starvation conditions.…”
Section: General Acclimation Responsesmentioning
confidence: 99%
“…5D) suggest that photosynthetically generated reactive oxygen species (ROS) may act as a destructive agent that drives 螖rpaA LD lethality. S. elongatus maintains a strict cellular redox balance and controls ROS using multiple systems, including modulation of phycobilisome abundance, glutathione redox control, and enzymatic ROS scavenging (46,47). Glutathione biosynthesis is particularly important for modulating redox state and counteracting ROS in cyanobacteria (46,48,49).…”
Section: Darkness Initiates Pigmentation Changes and Rapid Cell Deathmentioning
confidence: 99%
“…Cyanobacteria including Synechococcus spp., are known to be resistant to UV irradiation and oxygenic stress because they have to eliminate excess peroxide generated from photosynthesis (Latifi et al, 2009, Perelman et al, 2003. In a previous study, marine microorganisms such as cyanobacteria were shown to be transported by a Kosa event and comprised 20% of clone libraries obtained from air samples collected from Europe regions (Polymenakou at al.…”
Section: Cyanobacteriamentioning
confidence: 99%